Learning Cycle 7E: a Learning Model to Improve Junior High School Students’ Problem-Solving Skills in Science Subjects - Holongan, Fatimah Azzahra Nadia; Heryanti, Erna; Azrai, Eka Putri (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2024)
This research aims to determine the effect of the Learning Cycle 7E model on the problem-solving skills of junior high school students in the context of ecology and biodiversity in Indonesia. The research method used is a quasi-experimental design with a pretest-posttest nonequivalent control group design. The research sample consists of 64 students from Junior High School in East Jakarta, with each class comprising 32 students selected through simple random sampling. Based on the hypothesis test using the independent sample t-test, there is an effect of the Learning Cycle 7E model on the problem-solving skills of junior high school students in the context of ecology and biodiversity in Indonesia. The results of this study imply that the Learning Cycle 7E model can be an alternative for enhancing students' problem-solving skills in the context of ecology and biodiversity in Indonesia.